Modelling, simulation and analysis of a single rectangular microstrip patch antenna characteristic - Thelaha, Bin Haji Masri (2001)
This research investigated the microstrip patch antennas performance by studying and analyzing its characteristics and parameters that makes the microstrip elements resonates and radiates microwave signals into space. the literature, research, analysis and experiments through simulation is done qualitatively, if not quantitatively, to the characteristics of a square or rectangle microstrip antennas.